Fatores condicionantes do crescimento econômico de longo prazo a China: aspectos teóricos e investigação empírica - Andrade, Daniel Caixeta (2006)
The main goal of this dissertation is to empirically analyze China s growth experience during the period of 1978 to 2003. We have started with the hypothesis that China s economic growth during the last decades can be characterized by different aspects such as the investment rates (physical capital accumulation), a higher degree of financial and trade openness (stimulating exports and attracting external investments), a pegged exchange rate regime (favoring export performance) and human capital investments. The methodological procedures used were regression analysis, the estimation of a vector autoregressive (VAR) models using variance decomposition and impulse-response function instruments, Granger causality tests and the Johansen cointegration test. The results suggest that investment and exchange rate are the main determinants of China s economic growth for the period considered, which corroborates the initial hypothesis for these two variables. These results can not be understood as an indication that the continuity of China s economic performance should be centered only on capital physical accumulation and exchange rate policies. It is important that China can increase productivity based on more efficient investments on human capital and to rethink exchange rate management in the sense that is not clear yet the future impact of exchange rate flexibilization on China s economic growth once it moves towards a more flexible exchange rate regime.